Technological traits of the Chaku llama fibre before and after dehairing - Laime Huarcaya, Flor de María (2016)
Five technological characteristics of llama fiber were evaluated: average fibre diameter (AFD), the coefficient of fibre diameter (CVD), the comfort factor (CF), the fibre curvature (FC) and the spinning fineness (SF) before and after dehairing. Fibre samples (10 g) were collected from fleece of 227 llamas Chaku from the Apurimac region of Peru. Fiber samples before and after dehairing were analyzed with the OFDA 2000 (Optical Fibre Diameter Analyser). Sex and age (1-2 years and >2 years old) were considered as variables and the data was analyzed in a randomized complete design with a factorial arrangement. The results showed that dehaired llama fibre showed better quality, less AFD (0.70 μm), CVD (1.8%) and SF (1.06 μm) and better CF (2.74%) and FC (4.66°/mm). Sex had no significant effect on the technological characteristics of the fibre but younger animals had better quality fibre. It is concluded that dehairing and age have significant effects on lama fibre in relation to fineness and its variation, comfort factor, fibre curvature and spinning fineness.